Degradation of chondroitin sulfate: Mechanism of degradation, influence factors, structure-bioactivity relationship and application. (1st February 2023) - Wang, Kangyu; Qi, Liwei; Zhao, Laiyu; Liu, Jiqian; Guo, Yujie; Zhang, Chunhui
Abstract: Increasing studies focus on chondroitin sulfate (CS) degradation to improve its biological activity. The review mainly introduces the degradation methods of CS and their mechanisms. Studies have shown that different degradation methods can lead to different structures of low molecular weight chondroitin sulfate (LMCS). LMCS were prepared through β-elimination reaction, hydrolysis reaction, hydrogen abstraction reaction, and deamination reaction. The degradation of CS is affected by two aspects: the structure of CS (disaccharide composition and molecular weight) and the influence of degradation conditions (temperature, pH, degradation promoters, auxiliary conditions, and time). LMCS with different structures have different biological activities. In addition, degradation could also change CS's metabolism, such as absorption effects and gut microbiota. Thus, choosing the appropriate degradation method for CS development and utilization is very important. Graphical abstract: Unlabelled Image Highlights: The degradation methods and mechanisms of chondroitin sulfate (CS) were summarized. CS's degradation is affected by CS's structure and the degradation conditions. The structure-bioactivity relationship of degraded products was discussed. Degradation could change the absorption and metabolism of CS.